2016
DOI: 10.1371/journal.pone.0163135
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Knowledge on Fungal Communities in Directly Brined Aloreña de Málaga Green Olive Fermentations by Metabarcoding Analysis

Abstract: Nowadays, our knowledge of the fungal biodiversity in fermented vegetables is limited although these microorganisms could have a great influence on the quality and safety of this kind of food. This work uses a metagenetic approach to obtain basic knowledge of the fungal community ecology during the course of fermentation of natural Aloreña de Málaga table olives, from reception of raw material to edible fruits. For this purpose, samples of brines and fruits were collected from two industries in Guadalhorce Val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…Interestingly, both acids were strongly and positively correlated with the dominant yeast species, W. anomalus and C. nyonsensis , and bacterial species, C. diazotrophica , when pH drops in brine. C. nyonsensis was first isolated from Nyons table olives ( Casaregola et al, 2013 ) and since then has been identified in other olive fermentations ( Arroyo-López et al, 2016 ) while W. anomalus is frequently identified in olive fermentations ( Coton et al, 2006 ; Heperkan, 2013 ). OTUs related to C. diazotrophica dominated the fermentation early on, from 21 days, and remained among the most abundant bacterial species to the end of fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, both acids were strongly and positively correlated with the dominant yeast species, W. anomalus and C. nyonsensis , and bacterial species, C. diazotrophica , when pH drops in brine. C. nyonsensis was first isolated from Nyons table olives ( Casaregola et al, 2013 ) and since then has been identified in other olive fermentations ( Arroyo-López et al, 2016 ) while W. anomalus is frequently identified in olive fermentations ( Coton et al, 2006 ; Heperkan, 2013 ). OTUs related to C. diazotrophica dominated the fermentation early on, from 21 days, and remained among the most abundant bacterial species to the end of fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding table olive fermentations, culture-independent techniques have been extensively applied in the investigation of the microbial ecology of green olives, belonging mainly to Italian and Spanish varieties, fermented naturally or using the Spanish method [13][14][15][16][17][18]. Furthermore, these studies are usually performed with brines, not taking into consideration the study of the microbial population adhered to olive surface, which is finally the food intake by consumers [19]. However, information about the microbial diversity of natural black and Spanish-style green olive fermentations for Greek table olive varieties is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, their involvement is particularly important in natural olives, when fruits are not lye treated and phenolic compounds partly inhibit LAB development (Arroyo-López et al, 2012b ). Moreover, the presence of the various yeasts species was observed to vary even during the whole fermentation time (their number increased during the fermentation), because of and depending on their abilities to adapt to the evolution of the physico-chemical conditions of olives and brines (Pereira et al, 2015 ; Arroyo-López et al, 2016 ).…”
Section: Biotechnological Innovationsmentioning
confidence: 99%